Nanopore sequencing in non-human forensic genetics. Issue 3 (24th September 2021) - Ogden, Rob; Vasiljevic, Nina; Prost, Stefan
Abstract : The past decade has seen a rapid expansion of non-human forensic genetics coinciding with the development of 2nd and 3rd generation DNA sequencing technologies. Nanopore sequencing is one such technology that offers massively parallel sequencing at a fraction of the capital cost of other sequencing platforms. The application of nanopore sequencing to species identification has already been widely demonstrated in biomonitoring studies and has significant potential for non-human forensic casework, particularly in the area of wildlife forensics. This review examines nanopore sequencing technology and assesses its potential applications, advantages and drawbacks for use in non-human forensics, alongside other next-generation sequencing platforms and as a possible replacement to Sanger sequencing. We assess the specific challenges of sequence error rate and the standardisation of consensus sequence production, before discussing recent progress in the validation of nanopore sequencing for use in forensic casework. We conclude that nanopore sequencing may be able to play a considerable role in the future of non-human forensic genetics, especially for applications to wildlife law enforcement within emerging forensic laboratories.